Novel MLH1 nonsense variant in a patient with suspected Lynch syndrome - Nobue Takaiso; Issei Imoto; Toshihiko Matsumoto; Akiyo Yoshimura (Human Genome Variation)
Abstract Loss-of-function germline variants of MLH1 cause Lynch syndrome. Here, we present the case of a 43-year-old male patient diagnosed with cecal and transverse colon adenocarcinomas. The characteristics of the case met the revised Bethesda guidelines, and the tumors demonstrated a high frequency of microsatellite instability. Genetic testing for mismatch repair genes (indicative of Lynch syndrome) revealed a novel heterozygous germline pathogenic variant, NM_000249.4:c.856A>T/NP_000240.1:p.(Lys286Ter), in MLH1.